Effectiveness of health promotion utilizing word puzzle games in enhancing older adults' knowledge and attitudes regarding hypertension management - Mia Fatma Ekasari; Aan Nurhasanah; Eros Siti Suryati; Puspita Hanggit Lestari; Siti Badriah; Ahmad Jubaedi (Healthcare in Low-resource Settings)
Hypertension management plays a crucial role in influencing the health outcomes of the elderly with high blood pressure. Various health promotion strategies have been formulated for hypertension management. However, the result has not shown an optimal reduction in the number of hypertension sufferers. An effective health promotion, such as word puzzle games, needs to be developed. Word-based puzzle games can serve as engaging health promotion tools to improve hypertension-related health behaviors among older adults and enhance their cognitive abilities. This study aims to assess the effectiveness of a word puzzle game in enhancing the knowledge, attitudes, and practices of elderly individuals regarding hypertension management. A quasi-experimental approach with a pretest-posttest control group design was used. A total of 45 participants, both in intervention and control groups, were recruited through a purposive sampling technique. Data analysis involved descriptive techniques and inferential statistics using t-test models focusing on examining three variables: knowledge, attitudes, and behaviors. The result revealed statistically significant disparities in participants' knowledge (p=0.000), attitudes (p=0.001), and behaviors (p=0.001) between the experimental and control groups after implementing the word puzzle game intervention. Using word puzzle games as health promotion tools successfully enhances older adults' understanding, perspectives, and actions regarding hypertension management. These games might be employed to strengthen the ability of older individuals to control their high blood pressure.